Electronic ceramic powder as well as preparation method and application thereof

By coating the surface of aluminum powder with petal-shaped Al2O3/TiO2 micro/nano structures and doping with rare earth elements, the problems of agglomeration and high-temperature shrinkage of alumina powder have been solved, realizing the preparation of low-energy-consumption, high-performance electronic ceramic powder, which is suitable for modern electronics industry.

CN121318403APending Publication Date: 2026-01-13XUZHOU SOTENG MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511563084.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

Traditional high-purity alumina powder suffers from problems such as easy agglomeration, high-temperature shrinkage, and high sintering energy consumption, which affect the overall performance and cost of alumina ceramics.

Method used

A petal-shaped Al2O3/TiO2 micro/nano structure was coated on the surface of aluminum powder using the sol-gel method, and electronic ceramic powder was prepared by rare earth element doping, combined with wet ball milling and freeze drying techniques.

Benefits of technology

It effectively overcomes the problems of agglomeration and high-temperature shrinkage of alumina powder, reduces sintering energy consumption, and improves the overall performance and dispersibility of electronic ceramic powder, making it suitable for modern electronics industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121318403A_ABST
    Figure CN121318403A_ABST
Patent Text Reader

Abstract

The invention provides electronic ceramic powder as well as a preparation method and application thereof, and belongs to the technical field of electronic ceramics. The preparation method comprises the following steps: adding tetrabutyl titanate into aluminum sol, adding aluminum powder, uniformly mixing, drying, mixing with barium carbonate, strontium carbonate and lead carbonate, calcining, adding into rare earth doped titanium sol, calcining, and carrying out wet ball milling and freeze drying to obtain the electronic ceramic powder. The prepared electronic ceramic powder effectively overcomes the problems that traditional high-purity aluminum oxide powder is prone to agglomeration, high-temperature shrinkage, high in sintering energy consumption and the like, a product prepared from the prepared electronic ceramic powder is excellent in comprehensive performance, cost is reduced, operation is easy, and wide application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of electronic ceramics, in particular to an electronic ceramic powder and a preparation method and application thereof. BACKGROUND

[0002] Electronic ceramic powder is an important consumable material for electronic ceramics, which is made of ceramic materials and has magnetic and electrical properties, and has various types, including barium titanate base powder, MLCC formula powder, alumina ceramic powder and zirconia ceramic powder, and is widely used in communication, automotive electronics, consumer electronics and industry. Electronic ceramic powder is the most important raw material for manufacturing ceramic components, and its core requirements are purity, particle size and shape, etc.

[0003] In view of different market demands, new high-performance electronic ceramic powder materials are constantly being developed to meet the higher requirements of different electronic equipment on material performance, such as higher purity, finer particle size, better electrical performance, etc.

[0004] Alumina ceramic is a ceramic material mainly composed of alumina (Al2O3), which has good conductivity, mechanical strength and high temperature resistance. As a widely used ceramic, it is also widely used in the electronic industry as an electronic ceramic raw material because of its excellent thermal conductivity and conductivity.

[0005] However, the preparation method of alumina electronic ceramic has the technical problems that high-purity alumina powder is easy to agglomerate, the sintering temperature is high, the energy consumption is large, the shrinkage rate is high during high-temperature sintering, and the comprehensive performance is not good, which affects the subsequent use. Therefore, future research and development trends will pay more attention to green environmental protection, energy saving and consumption reduction, and integration with new electronic technologies. SUMMARY

[0006] The purpose of the present application is to provide an electronic ceramic powder and a preparation method and application thereof, which effectively overcome the problems of easy agglomeration, high-temperature shrinkage, high sintering energy consumption, etc. of traditional high-purity alumina powder, and the electronic ceramic powder prepared has excellent comprehensive performance, low cost, easy operation, and wide application prospect.

[0007] The technical solution of the present application is as follows: The present application provides a preparation method of an electronic ceramic powder, which comprises the following steps: adding tetrabutyl titanate into an aluminum sol, adding aluminum powder, mixing uniformly, drying, mixing with barium carbonate, strontium carbonate and lead carbonate, calcining, then adding rare earth doped titanium sol, calcining, wet ball milling, freeze-drying, and obtaining the electronic ceramic powder.

[0008] As a further improvement of the present application, the following steps are included: S1. Preparation of aluminum sol: aluminum salt is dissolved in water, heated and stirred to mix uniformly, ammonia water is added dropwise, and the solution is stirred and heated to adjust the pH value, and stirred and reacted to prepare aluminum sol; S2. Preparation of composite: tetrabutyl titanate and water are added to the aluminum sol, stirred and reacted, then aluminum powder is added, stirred and mixed uniformly, dried, and ball milled to prepare the composite; S3. Calcination: the composite, barium carbonate, strontium carbonate, and lead carbonate are mixed uniformly, calcined in an air atmosphere, and ball milled to prepare barium / strontium / lead titanate deposited alumina / titania coated aluminum powder; S4. Preparation of composite rare earth sol: tetrabutyl titanate is dissolved in ethanol, acetic acid is added and stirred, then lanthanum salt, yttrium salt, and lutetium salt are added and stirred, and barium / strontium / lead titanate deposited alumina / titania coated aluminum powder is added and stirred to mix uniformly to form the composite rare earth sol; S5. Second calcination: the composite rare earth sol is calcined in an air atmosphere to prepare the composite; S6. Post-treatment: the composite is wet ball milled and freeze-dried to prepare the electronic ceramic powder.

[0009] As a further improvement of the present application, the aluminum salt in step S1 is aluminum nitrate, the mass ratio of the aluminum salt to ammonia water is 1:2-4, the pH value of the solution is adjusted to 4.5-5, the heating temperature is 55-65℃, the temperature is raised to 75-85℃, the time for temperature maintenance and stirring is 0.5-1.5h, the time for stirring and reaction is 1-3h, and the concentration of ammonia water is 5-10wt%.

[0010] As a further improvement of the present application, the mass ratio of the aluminum sol, tetrabutyl titanate, and aluminum powder in step S2 is 100:4-6:2-3, and the time for stirring and reaction is 1-3h.

[0011] As a further improvement of the present application, the mass ratio of the composite, barium carbonate, strontium carbonate, and lead carbonate in step S3 is 10:1-2:0.2-0.5:0.3-0.4, the calcination temperature is 1250-1350℃, and the time is 1-3h.

[0012] As a further improvement of the present application, the mass ratio of tetrabutyl titanate, acetic acid, lanthanum salt, yttrium salt, lutetium salt, and barium / strontium / lead titanate deposited alumina / titania coated aluminum powder in step S4 is 3-5:4-6:0.5-1:0.2-0.5:0.4-0.7:15-20, the lanthanum salt is lanthanum chloride or lanthanum nitrate, the yttrium salt is yttrium chloride, and the lutetium salt is lutetium nitrate.

[0013] As a further improvement of the present application, the calcination temperature in step S5 is 500-600℃, and the time is 1-3h.

[0014] As a further improvement of the present invention, the wet ball milling time in step S6 is 1-3 hours.

[0015] This invention further protects an electronic ceramic powder prepared by the above-described preparation method.

[0016] This invention further protects the application of the above-mentioned electronic ceramic powder in the preparation of electronic components.

[0017] The present invention has the following beneficial effects: This invention employs a sol-gel method to prepare petal-shaped Al2O3 / TiO2 micro / nanostructures coated on the surface of aluminum powder. Due to the presence of pores, the coated aluminum powder can oxidize to alumina at high temperatures, accompanied by volume expansion, which offsets shrinkage and overcomes the problem of high shrinkage rate during high-temperature sintering of alumina powder. Coating the surface of aluminum powder with petal-shaped Al2O3 / TiO2 micro / nanostructures reduces interparticle friction during molding, overcomes the problem of powder agglomeration, and simultaneously improves compatibility with organic binders.

[0018] Furthermore, the TiO2 component on the surface can react with barium carbonate, strontium carbonate, and lead carbonate during solid-state calcination to form barium titanate / strontium / lead complexes. Barium titanate exhibits excellent ferroelectric and piezoelectric properties, extremely high dielectric constant, significant positive electrothermal effect, and good semiconductor characteristics. Additionally, the use of rare earth elements to enhance the properties of Ba... 2+ Doping at the curvature of barium titanate (BTi) can produce n-type semiconductor ceramics, which can be used to manufacture positive temperature coefficient (PTC) thermistors. Their resistance increases dramatically by several orders of magnitude near the Curie point, making them widely used in overcurrent protection, temperature sensing, and self-regulating heating elements. Strontium titanate possesses high and stable linear dielectric properties, quantum paraelectric characteristics, and excellent lattice matching. It can be used as a performance modifier; when forming a solid solution with barium titanate, it can effectively lower the Curie temperature, widen the operating temperature range, and regulate the temperature stability of the dielectric constant and piezoelectric coefficient. Lead titanate has an extremely high Curie temperature and large anisotropy. By adjusting the content of each component in the barium titanate / strontium / lead titanate composite, the piezoelectric properties, electromechanical coupling coefficient, and dielectric constant of the prepared material can reach peak values, resulting in electronic ceramic powders with performance meeting the stringent requirements of the modern electronics industry.

[0019] Furthermore, this invention loads a rare earth lanthanum oxide / yttrium oxide / lutetium oxide composite onto the surface of barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder. In the alumina, La... 3+ Al replacement 3+ At this time, oxygen vacancies are generated to maintain charge balance, accelerating oxygen ion diffusion. In barium titanate, Y 3+Doping creates defects and generates oxygen vacancies, promoting the migration of titanium ions. Meanwhile, Y2O3 and Lu2O3 can form a low-melting-point liquid phase with the ceramic matrix or impurities, significantly reducing the sintering temperature. The combined effect of the three rare earth oxides achieves synergistic performance through multi-electrode ion interaction, thereby greatly reducing the energy consumption in the preparation of electronic ceramics and having broad application value.

[0020] This invention obtains electronic ceramic powder by wet ball milling and freeze drying of the prepared composite. On the one hand, ball milling can obtain powder with small and uniform particle size. On the other hand, after ball milling breaks up hard agglomerates, freeze drying is performed immediately to avoid secondary agglomeration caused by capillary tension, resulting in a decrease in bulk density and excellent redispersibility. This effectively avoids the problem of easy agglomeration of traditional high-purity alumina powder.

[0021] The electronic ceramic powder prepared by this invention effectively overcomes the problems of easy agglomeration, high-temperature shrinkage, and high sintering energy consumption of traditional high-purity alumina powder. The electronic ceramic powder prepared by this invention has excellent comprehensive performance, reduced cost, and is easy to operate, and has broad application prospects. Attached Figure Description

[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 This is a SEM image of the barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder prepared in Example 1. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] Example 1 This embodiment provides a method for preparing electronic ceramic powder, including the following steps: S1. Preparation of aluminum sol: Dissolve 10g of aluminum nitrate in 50mL of water, heat to 55℃, stir and mix for 15min, add 20g of 7wt% ammonia water dropwise, keep warm and stir for 0.5h, raise the temperature to 75℃, adjust the pH of the solution to 4.5, stir and react for 1h to obtain aluminum sol; S2. Preparation of the composite: Add 4g tetrabutyl titanate, 5mL water and 20mL ethanol to 100g aluminum sol, stir and react for 1h, then add 2g aluminum powder, stir and mix for 30min, dry, and ball mill for 1h to obtain the composite. S3. Calcination: Mix 10g of the composite, 1g of barium carbonate, 0.2g of strontium carbonate and 0.3g of lead carbonate evenly, calcine at 1250℃ for 1h in air, and ball mill for 1h to obtain barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder. S4. Preparation of composite rare earth sol: Dissolve 3g tetrabutyl titanate in 30mL ethanol, add 4g acetic acid, stir, then add 0.5g lanthanum chloride, 0.2g yttrium chloride, 0.4g lutetium nitrate and 4g polyethylene glycol, stir, add 15g barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder, stir and mix for 2h to form composite rare earth sol; S5. Second calcination: The composite rare earth sol was calcined in air at 500°C for 1 hour to obtain the composite. S6. Post-processing: The composite was wet-ball-milled for 1 hour and freeze-dried to obtain electronic ceramic powder.

[0026] Example 2 This embodiment provides a method for preparing electronic ceramic powder, including the following steps: S1. Preparation of aluminum sol: Dissolve 10g of aluminum nitrate in 50mL of water, heat to 65℃, stir and mix for 15min, add 40g of 7wt% ammonia water dropwise, keep warm and stir for 1.5h, raise the temperature to 85℃, adjust the pH of the solution to 5, stir and react for 3h to obtain aluminum sol; S2. Preparation of the composite: Add 6g tetrabutyl titanate, 10mL water and 20mL ethanol to 100g aluminum sol, stir and react for 3h, then add 3g aluminum powder, stir and mix for 30min, dry, and ball mill for 1h to obtain the composite. S3. Calcination: Mix 10g of the composite, 2g of barium carbonate, 0.5g of strontium carbonate and 0.4g of lead carbonate evenly, calcine at 1350℃ for 3h in air, and ball mill for 1h to obtain barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder. Figure 1 The image shows a SEM image of the prepared barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder. As can be seen from the image, the surface of the powder has a wrinkled, petal-like structure.

[0027] S4. Preparation of composite rare earth sol: Dissolve 5g tetrabutyl titanate in 30mL ethanol, add 6g acetic acid, stir, then add 1g lanthanum nitrate, 0.5g yttrium chloride, 0.7g lutetium nitrate and 4g polyethylene glycol, stir, add 20g barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder, stir and mix for 2h to form composite rare earth sol; S5. Second calcination: The composite rare earth sol was calcined in air at 600°C for 3 hours to obtain the composite. S6. Post-processing: The composite was wet-ball-milled for 3 hours and freeze-dried to obtain electronic ceramic powder.

[0028] Example 3 This embodiment provides a method for preparing electronic ceramic powder, including the following steps: S1. Preparation of aluminum sol: Dissolve 10g of aluminum nitrate in 50mL of water, heat to 60℃, stir and mix for 15min, add 30g of 7wt% ammonia water dropwise, keep warm and stir for 1h, raise the temperature to 80℃, adjust the pH of the solution to 4.7, stir and react for 2h to obtain aluminum sol; S2. Preparation of the composite: Add 5g tetrabutyl titanate, 7mL water and 20mL ethanol to 100g aluminum sol, stir and react for 2h, then add 2.5g aluminum powder, stir and mix for 30min, dry, and ball mill for 1h to obtain the composite. S3. Calcination: Mix 10g of the composite, 1.5g of barium carbonate, 0.35g of strontium carbonate and 0.35g of lead carbonate evenly, calcine at 1300℃ for 2h in air, and ball mill for 1h to obtain barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder. S4. Preparation of composite rare earth sol: Dissolve 4g tetrabutyl titanate in 30mL ethanol, add 5g acetic acid, stir, then add 0.7g lanthanum chloride, 0.35g yttrium chloride, 0.5g lutetium nitrate and 4g polyethylene glycol, stir, add 17g barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder, stir and mix for 2h to form composite rare earth sol; S5. Second calcination: The composite rare earth sol was calcined in air at 550°C for 2 hours to obtain the composite. S6. Post-processing: The composite was wet-ball-milled for 2 hours and freeze-dried to obtain electronic ceramic powder.

[0029] Comparative Example 1 The difference from Example 3 is that aluminum powder was not added in step S2.

[0030] Specifically as follows: S1. Preparation of aluminum sol: Dissolve 10g of aluminum nitrate in 50mL of water, heat to 60℃, stir and mix for 15min, add 30g of 7wt% ammonia water dropwise, keep warm and stir for 1h, raise the temperature to 80℃, adjust the pH of the solution to 4.7, stir and react for 2h to obtain aluminum sol; S2. Preparation of the composite: Add 5g tetrabutyl titanate, 7mL water and 20mL ethanol to 100g aluminum sol, stir for 2h, dry, and ball mill for 1h to obtain the composite; S3. Calcination: Mix 10g of the composite, 1.5g of barium carbonate, 0.35g of strontium carbonate and 0.35g of lead carbonate evenly, calcine at 1300℃ for 2h in air, and ball mill for 1h to obtain barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder. S4. Preparation of composite rare earth sol: Dissolve 4g tetrabutyl titanate in 30mL ethanol, add 5g acetic acid, stir, then add 0.7g lanthanum chloride, 0.35g yttrium chloride, 0.5g lutetium nitrate and 4g polyethylene glycol, stir, add 17g barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder, stir and mix for 2h to form composite rare earth sol; S5. Second calcination: The composite rare earth sol was calcined in air at 550°C for 2 hours to obtain the composite. S6. Post-processing: The composite was wet-ball-milled for 2 hours and freeze-dried to obtain electronic ceramic powder.

[0031] Comparative Example 2 The difference from Example 3 is that barium carbonate was not added in step S3.

[0032] Specifically as follows: S1. Preparation of aluminum sol: Dissolve 10g of aluminum nitrate in 50mL of water, heat to 60℃, stir and mix for 15min, add 30g of 7wt% ammonia water dropwise, keep warm and stir for 1h, raise the temperature to 80℃, adjust the pH of the solution to 4.7, stir and react for 2h to obtain aluminum sol; S2. Preparation of the composite: Add 5g tetrabutyl titanate, 7mL water and 20mL ethanol to 100g aluminum sol, stir and react for 2h, then add 2.5g aluminum powder, stir and mix for 30min, dry, and ball mill for 1h to obtain the composite. S3. Calcination: Mix 10g of the composite, 0.35g of strontium carbonate and 0.35g of lead carbonate evenly, calcine at 1300℃ for 2h in air, and ball mill for 1h to obtain strontium titanate / lead deposited alumina / titanium oxide coated aluminum powder. S4. Preparation of composite rare earth sol: Dissolve 4g tetrabutyl titanate in 30mL ethanol, add 5g acetic acid, stir, then add 0.7g lanthanum chloride, 0.35g yttrium chloride, 0.5g lutetium nitrate and 4g polyethylene glycol, stir, add 17g strontium titanate / lead deposited alumina / titanium oxide coated aluminum powder, stir and mix for 2h to form composite rare earth sol; S5. Second calcination: The composite rare earth sol was calcined in air at 550°C for 2 hours to obtain the composite. S6. Post-processing: The composite was wet-ball-milled for 2 hours and freeze-dried to obtain electronic ceramic powder.

[0033] Comparative Example 3 The difference from Example 3 is that strontium carbonate was not added in step S3.

[0034] Specifically as follows: S1. Preparation of aluminum sol: Dissolve 10g of aluminum nitrate in 50mL of water, heat to 60℃, stir and mix for 15min, add 30g of 7wt% ammonia water dropwise, keep warm and stir for 1h, raise the temperature to 80℃, adjust the pH of the solution to 4.7, stir and react for 2h to obtain aluminum sol; S2. Preparation of the composite: Add 5g tetrabutyl titanate, 7mL water and 20mL ethanol to 100g aluminum sol, stir and react for 2h, then add 2.5g aluminum powder, stir and mix for 30min, dry, and ball mill for 1h to obtain the composite. S3. Calcination: Mix 10g of the composite, 1.5g of barium carbonate and 0.35g of lead carbonate evenly, calcine at 1300℃ for 2h in air, and ball mill for 1h to obtain barium titanate / lead deposited alumina / titanium oxide coated aluminum powder. S4. Preparation of composite rare earth sol: Dissolve 4g tetrabutyl titanate in 30mL ethanol, add 5g acetic acid, stir, then add 0.7g lanthanum chloride, 0.35g yttrium chloride, 0.5g lutetium nitrate and 4g polyethylene glycol, stir, add 17g barium titanate / lead deposited alumina / titanium oxide coated aluminum powder, stir and mix for 2h to form composite rare earth sol; S5. Second calcination: The composite rare earth sol was calcined in air at 550°C for 2 hours to obtain the composite. S6. Post-processing: The composite was wet-ball-milled for 2 hours and freeze-dried to obtain electronic ceramic powder.

[0035] Comparative Example 4 The difference from Example 3 is that lead carbonate was not added in step S3.

[0036] Specifically, as follows: S1. Preparation of aluminum sol: Dissolve 10g of aluminum nitrate in 50mL of water, heat to 60℃, stir and mix for 15min, add 30g of 7wt% ammonia water dropwise, keep warm and stir for 1h, raise the temperature to 80℃, adjust the pH of the solution to 4.7, stir and react for 2h to obtain aluminum sol; S2. Preparation of the composite: Add 5g tetrabutyl titanate, 7mL water and 20mL ethanol to 100g aluminum sol, stir and react for 2h, then add 2.5g aluminum powder, stir and mix for 30min, dry, and ball mill for 1h to obtain the composite. S3. Calcination: Mix 10g of the composite, 1.5g of barium carbonate and 0.35g of strontium carbonate evenly, calcine at 1300℃ for 2h in air, and ball mill for 1h to obtain barium titanate / strontium deposited alumina / titanium oxide coated aluminum powder; S4. Preparation of composite rare earth sol: Dissolve 4g tetrabutyl titanate in 30mL ethanol, add 5g acetic acid, stir, then add 0.7g lanthanum chloride, 0.35g yttrium chloride, 0.5g lutetium nitrate and 4g polyethylene glycol, stir, add 17g barium titanate / strontium deposited alumina / titanium oxide coated aluminum powder, stir and mix for 2h to form composite rare earth sol; S5. Second calcination: The composite rare earth sol was calcined in air at 550°C for 2 hours to obtain the composite. S6. Post-processing: The composite was wet-ball-milled for 2 hours and freeze-dried to obtain electronic ceramic powder.

[0037] Comparative Example 5 The difference from Example 3 is that steps S4 and S5 were not performed.

[0038] Specifically as follows: S1. Preparation of aluminum sol: Dissolve 10g of aluminum nitrate in 50mL of water, heat to 60℃, stir and mix for 15min, add 30g of 7wt% ammonia water dropwise, keep warm and stir for 1h, raise the temperature to 80℃, adjust the pH of the solution to 4.7, stir and react for 2h to obtain aluminum sol; S2. Preparation of the composite: Add 5g tetrabutyl titanate, 7mL water and 20mL ethanol to 100g aluminum sol, stir and react for 2h, then add 2.5g aluminum powder, stir and mix for 30min, dry, and ball mill for 1h to obtain the composite. S3. Calcination: Mix 10g of the composite, 1.5g of barium carbonate, 0.35g of strontium carbonate and 0.35g of lead carbonate evenly, calcine at 1300℃ for 2h in air, and ball mill for 1h to obtain barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder. S4. Post-processing: The barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder is wet ball-milled for 2 hours and freeze-dried to obtain electronic ceramic powder.

[0039] Comparative Example 6 The difference from Example 3 is that step S6 was not performed.

[0040] Specifically as follows: S1. Preparation of aluminum sol: Dissolve 10g of aluminum nitrate in 50mL of water, heat to 60℃, stir and mix for 15min, add 30g of 7wt% ammonia water dropwise, keep warm and stir for 1h, raise the temperature to 80℃, adjust the pH of the solution to 4.7, stir and react for 2h to obtain aluminum sol; S2. Preparation of the composite: Add 5g tetrabutyl titanate, 7mL water and 20mL ethanol to 100g aluminum sol, stir and react for 2h, then add 2.5g aluminum powder, stir and mix for 30min, dry, and ball mill for 1h to obtain the composite. S3. Calcination: Mix 10g of the composite, 1.5g of barium carbonate, 0.35g of strontium carbonate and 0.35g of lead carbonate evenly, calcine at 1300℃ for 2h in air, and ball mill for 1h to obtain barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder. S4. Preparation of composite rare earth sol: Dissolve 4g tetrabutyl titanate in 30mL ethanol, add 5g acetic acid, stir, then add 0.7g lanthanum chloride, 0.35g yttrium chloride, 0.5g lutetium nitrate and 4g polyethylene glycol, stir, add 17g barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder, stir and mix for 2h to form composite rare earth sol; S5. Second calcination: The composite rare earth sol is calcined at 550°C for 2 hours in air and then ball-milled for 2 hours to obtain the composite, which is the electronic ceramic powder.

[0041] Test Example 1 The loose bulk density of the electronic ceramic powders prepared in Examples 1-3 and Comparative Example 6, as well as commercially available alumina ceramic powder (Xuancheng Jingrui New Materials), was tested, and the results are shown in Table 1.

[0042] Table 1

[0043] As can be seen from the table above, the electronic ceramic powders prepared in Examples 1-3 of the present invention have low bulk density and excellent dispersibility, effectively avoiding the problem of easy agglomeration of traditional high-purity alumina powder.

[0044] Test Example 2 The electronic ceramic powders prepared in Examples 1-3 and Comparative Example 1, as well as commercially available alumina ceramic powder (Xuancheng Jingrui New Materials), were dried and pressed into blanks at 100 MPa. They were then sintered at 1200℃ for 2 hours. The performance was tested after sintering, and the results are shown in Table 2.

[0045] Table 2

[0046] As can be seen from the table above, the electronic ceramic powders prepared in Examples 1-3 of this invention have a low shrinkage rate during high-temperature sintering.

[0047] Test Example 3 The electronic ceramic powders obtained in Examples 1-3 and Comparative Examples 1-6 were dried and pressed into blanks at 100 MPa. They were then sintered at 1200℃ for 2 hours (Comparative Example 5 was sintered at 1600℃ for 2 hours). After sintering, the performance of alumina ceramic substrates for thick film integrated circuits was tested according to GB / T 14619-2013. The results are shown in Table 3.

[0048] Table 3

[0049] As can be seen from the table above, the green bodies obtained by sintering the electronic ceramic powder prepared in Examples 1-3 of the present invention have good comprehensive performance.

[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing electronic ceramic powder, characterized in that, Tetrabutyl titanate was added to aluminum sol, along with aluminum powder, and mixed evenly. The mixture was then dried and calcined with barium carbonate, strontium carbonate, and lead carbonate. The mixture was then added to rare earth-doped titanium sol and calcined. After wet ball milling and freeze drying, electronic ceramic powder was obtained.

2. The preparation method according to claim 1, characterized in that, Includes the following steps: S1. Preparation of aluminum sol: Dissolve aluminum salt in water, heat and stir until homogeneous, add ammonia dropwise, keep warm and stir, raise the temperature, adjust the pH of the solution, stir the reaction to obtain aluminum sol; S2. Preparation of the composite: Tetrabutyl titanate and water were added to aluminum sol and stirred to react. Then aluminum powder was added, stirred and mixed evenly, dried, and ball-milled to obtain the composite. S3. Calcination: The composite, barium carbonate, strontium carbonate, and lead carbonate are mixed evenly, calcined in air, and ball-milled to obtain barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder; S4. Preparation of composite rare earth sol: Tetrabutyl titanate is dissolved in ethanol, acetic acid is added and stirred, then lanthanum salt, yttrium salt and lutetium salt are added and stirred, barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder is added and stirred and mixed evenly to form composite rare earth sol; S5. Second calcination: The composite rare earth sol is calcined in air to obtain the composite. S6. Post-processing: The composite is wet-ball-milled and freeze-dried to obtain electronic ceramic powder.

3. The preparation method according to claim 2, characterized in that, In step S1, the aluminum salt is aluminum nitrate, the mass ratio of the aluminum salt to ammonia is 1:2-4, the pH of the solution is adjusted to 4.5-5, the heating temperature is 55-65℃, the temperature is raised to 75-85℃, the holding and stirring time is 0.5-1.5h, the stirring reaction time is 1-3h, and the concentration of ammonia is 5-10wt%.

4. The preparation method according to claim 2, characterized in that, In step S2, the mass ratio of aluminum sol, tetrabutyl titanate, and aluminum powder is 100:4-6:2-3, and the stirring reaction time is 1-3 hours.

5. The preparation method according to claim 2, characterized in that, In step S3, the mass ratio of the complex, barium carbonate, strontium carbonate, and lead carbonate is 10:1-2:0.2-0.5:0.3-0.4, and the calcination temperature is 1250-1350℃ for 1-3 hours.

6. The preparation method according to claim 2, characterized in that, In step S4, the mass ratio of tetrabutyl titanate, acetic acid, lanthanum salt, yttrium salt, lutetium salt, and barium titanate / strontium / lead deposited alumina / titanium oxide coated aluminum powder is 3-5:4-6:0.5-1:0.2-0.5:0.4-0.7:15-20. The lanthanum salt is lanthanum chloride or lanthanum nitrate, the yttrium salt is yttrium chloride, and the lutetium salt is lutetium nitrate.

7. The preparation method according to claim 2, characterized in that, The calcination temperature in step S5 is 500-600℃, and the time is 1-3h.

8. The preparation method according to claim 2, characterized in that, The wet ball milling time in step S6 is 1-3 hours.

9. An electronic ceramic powder prepared by the preparation method according to any one of claims 1-8.

10. The application of the electronic ceramic powder as described in claim 9 in the preparation of electronic components.